Agglomeration and Hours Worked - Rosenthal, Stuart S.; Strange, William C. (The Review of Economics and Statistics, 2008)
This paper establishes the existence of a previously overlooked relationship between agglomeration and hours worked. Among nonprofessionals, hours worked decrease with the density of workers in the same occupation. Among professionals, the relationship is positive. This relationship is stronger for the young than for the middle-aged. Moreover, young professional hours worked are especially sensitive to the presence of rivals. The paper shows that these patterns are consistent with the selection of hard workers into cities and with the high productivity of agglomerated labor. The behavior of young professionals is also consistent with the presence of keen rivalry in larger markets, a kind of urban rat race.